Cupid doesn't flip hamburgers - Dadey, Debbie; Gurney, John Steven, 1962-; Jones, Marcia Thornton (New York : Scholastic, 1995)
The Bailey School kids decide to investigate when it appears that the new cook in the school cafeteria might really be Cupid.
"A Little Apple paperback.".
3.6
3-6
Keywords: Cooks -- Juvenile fiction; Schools -- Juvenile fiction; Cooks -- Fiction; Schools -- Fiction; Cooks -- Fiction; School stories